The Indonesian economic Constitution from the perspective of Franz Böhm and Walter Eucken for a just Market - Nurul Fazri Elfikri; Muhamad Khairun Kurniawan Kadir; Mohamad Hidayat Muhtar; Sofyan Piyo; Fitran Amrain; Zainal Abdul Aziz Hadju (JUSTISI, 2026)
This study aims to reconstruct the implementation of Article 33 of the 1945 Constitution through the framework of Ordnungspolitik developed by Franz Böhm and Walter Eucken. The study is grounded in the existence of imbalances in the normative, institutional, and functional dimensions of Indonesia’s economic system, which hinder the realization of the principles of solidarity and social justice. This study uses a normative legal methodology with a conceptual and comparative approach to legal thought. The analysis examines the comprehensive text of the amendments to the 1945 Constitution, sectoral regulations (such as the Job Creation Law and the Mining and Energy Law), as well as Constitutional Court rulings related to the economy. Data is analyzed qualitatively to align the principles of the German economic order (Ordoliberalism) with the values of the Indonesian Constitution. The novelty of this study lies in offering a new interpretive model for Article 33 of the 1945 Constitution by positioning the state as the architect of the market order (rather than merely a passive actor or regulator). Its innovation lies in integrating the substantive rule of law of Ordnungspolitik to limit the concentration of private economic power, which often distorts the constitutional mandate. The results show that Ordnungspolitik provides operational instruments for Indonesia to achieve distributive justice through two main channels: (1) strengthening the independence of competition oversight agencies to the level of constitutional institutions, and (2) codifying economic laws that guarantee market access rights for small businesses. This interpretation shifts the paradigm of Article 33 from mere symbolism regarding “cooperatives” to a binding norm that obligates the state to undertake structural interventions to maintain market integrity. The conclusion is that integrating the principles of Ordnungspolitik into the national legal system can serve as a solution to Indonesia’s economic institutional failures. This study recommends restructuring economic public policy to prioritize healthy competition and the protection of social rights as an inseparable legal order.